Health Beliefs Related to Diabetes Mellitus Prevention among Adolescents in Saudi Arabia - Al-Mutairi, Reem L. (Sultan Qaboos Univ Med J, 2015)
OBJECTIVES: The incidence of type 2 diabetes mellitus (T2DM) is growing rapidly in the Saudi population. The purpose of this study was to assess the constructs of the health belief model (HBM) as they relate to T2DM lifestyle and prevention behaviours among adolescents. METHODS: A cross-sectional study was conducted between May and October 2013 among 426 non-diabetic secondary school students from randomly selected schools in Riyadh, Saudi Arabia. An Arabic version of an adapted English language questionnaire was used to assess knowledge and attitudes related to the severity and prevention of T2DM. A preventative behaviour assessment was also conducted to assess physical activity and dietary habits. RESULTS: The majority of the students (63.4%) had at least one diabetic family member. Obesity was more frequent in males compared to females (P = 0.013). Awareness about the importance of maintaining a healthy body weight to prevent T2DM was lower in males than females (P = 0.037), although males engaged in routine exercise more often (P = 0.001). Males were less likely than females to recognise the risks for T2DM, including obesity (P = 0.030), heredity (P = 0.013) and high fat intake (P = 0.001). CONCLUSION: An alarmingly high number of Saudi students were unaware of T2DM severity and associated risk factors. Female students were more aware of the benefits of T2DM preventative lifestyle behaviours than males, although males engaged in routine exercise more often. Raising adolescents’ awareness about the primary prevention strategies for T2DM should be a public health priority in Saudi Arabia. The HBM could inform further research on diabetes prevention among Saudi adolescents.